2008
DOI: 10.1590/s1517-83822008000400035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on the inactivation of aflatoxin B1 in food and feed crops

Abstract: Samples of food crops (peanut, peeled pistachio, unpeeled pistachio, rice, and corn) and feed (barley, bran, corn) were autoclave-sterilized, and inoculated with 10 6 of spore suspension of an isolate of Aspergillus flavus fungus known to produce aflatoxin B1 (AFB1) . Following a 10-day period of incubation at 27 C to allow for fungal growth, food and feed samples were irradiated with gamma radiation at the doses 4, 6, and 10 kGy. Results indicated that degradation of AFB1 was positively correlated with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 11 publications
(21 reference statements)
5
36
0
1
Order By: Relevance
“…However, there was no reduction in the mycotoxin content at doses less than 10 kGy. In agreement with our results, Ghanem, Orfi, and Shamma (2008) reported that degradation of AFB 1 in food crops (peanut, peeled pistachio, unpeeled pistachio, rice, and corn) and feed (barley, bran, corn) was positively correlated with increases in the applied dose of gamma ray. In a related study, doses of 15, 20, 25 and 30 kGy were used to destroy aflatoxin B 1 in peanut sample by 55-74% (Prado et al, 2003).…”
Section: Effects Of Gamma Ray Doses and Mycotoxin Concentrationsupporting
confidence: 93%
“…However, there was no reduction in the mycotoxin content at doses less than 10 kGy. In agreement with our results, Ghanem, Orfi, and Shamma (2008) reported that degradation of AFB 1 in food crops (peanut, peeled pistachio, unpeeled pistachio, rice, and corn) and feed (barley, bran, corn) was positively correlated with increases in the applied dose of gamma ray. In a related study, doses of 15, 20, 25 and 30 kGy were used to destroy aflatoxin B 1 in peanut sample by 55-74% (Prado et al, 2003).…”
Section: Effects Of Gamma Ray Doses and Mycotoxin Concentrationsupporting
confidence: 93%
“…Other decontamination approaches include food and feed processing, such as thermal inactivation, irradiation, solvent extraction, mechanical separation, density segregation, and reduction in bioavailable aflatoxin by selective chemisorptions. Although such treatments almost completely reduce mycotoxin concentrations, these chemicals also reduce nutrient concentrations (4,9,15). Evidently, the best decontaminant should be detoxification by biodegradation, which might remove mycotoxins under mild conditions.…”
mentioning
confidence: 99%
“…The aflatoxin reduction in coffee bean during roasting was also found to be dependent on the type and temperature of roasting with moderate reductions of approximately 42 to 56% (Bullerman & Bianchini, 2007). Gamma irradiation was also reported to decrease the total aflatoxins and aflatoxin B 1 levels gradually, with increase in gamma irradiation dose from 0 to 10 kGy (Ghanem, Orfi, & Shamma, 2008;Gupta, Bajpai, Mishra, Saxena, & Singh, 2009;Kumari, et al, 2009). However, in another study a 24-43% reduction in aflatoxin contamination was observed with irradiation at 60 kGY (Jalili, Jinap, & Noranizan, 2010).…”
Section: Other Foodsmentioning
confidence: 91%